2021
DOI: 10.3390/ma14051102
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Nano-Auger Probe of Chloride-Ions during CH3NH3PbI3−xClx Perovskite Formation

Abstract: Organo-halide perovskite solar cells (PSCs) have emerged as next-generation photovoltaics, owing to their high power-conversion efficiency (PCE), lower production cost, and high flexibility. ABX3-structured methylammonium lead triiodide (CH3NH3PbI3 or MAPbI3) perovskite is a widely studied light-absorbing material in PSCs. Interestingly, a small amount of chlorine incorporation into MAPbI3 increases charge carrier diffusion lengths (from 129 nm to 1069 nm), which enables planar structured PSCs with high PCEs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Still, chlorine can be incorporated in the MAPbI 3 perovskite crystal at relatively low concentration levels below 3–4% without significantly affecting the band gap . Even at such low concentrations, Cl doping can dramatically improve charge transport. , Starting from PbCl 2 , our analysis proposes that there may be a certain amount of chlorine still within the final MAPbI 3 perovskite, acting as an unintentional dopant, in line with experimental observations on PbCl 2 -derived MAPbI 3 . , On the other hand, as MAPbI 3 crystal growth is energetically beneficial, the presence of chlorine coordinated to Pb centers can substantially retard the crystallization dynamics, as reported by experiments. , Even though chlorine-rich phases are not to be expected in the perovskite crystal, chlorine may be incorporated within grain boundaries and grain surfaces. Previous studies showed reduced electron–hole recombination upon replacing iodine ions with chlorine ions at grain boundaries. , Finally, a direct correlation of the amount of [PbI 4 ] 2– in the precursor solution with the trap density in the final perovskite was reported .…”
Section: Resultssupporting
confidence: 80%
“…Still, chlorine can be incorporated in the MAPbI 3 perovskite crystal at relatively low concentration levels below 3–4% without significantly affecting the band gap . Even at such low concentrations, Cl doping can dramatically improve charge transport. , Starting from PbCl 2 , our analysis proposes that there may be a certain amount of chlorine still within the final MAPbI 3 perovskite, acting as an unintentional dopant, in line with experimental observations on PbCl 2 -derived MAPbI 3 . , On the other hand, as MAPbI 3 crystal growth is energetically beneficial, the presence of chlorine coordinated to Pb centers can substantially retard the crystallization dynamics, as reported by experiments. , Even though chlorine-rich phases are not to be expected in the perovskite crystal, chlorine may be incorporated within grain boundaries and grain surfaces. Previous studies showed reduced electron–hole recombination upon replacing iodine ions with chlorine ions at grain boundaries. , Finally, a direct correlation of the amount of [PbI 4 ] 2– in the precursor solution with the trap density in the final perovskite was reported .…”
Section: Resultssupporting
confidence: 80%
“…GB resistivity [60,61] PL carriers lifetime at GBs [62][63][64][65] AES/X-ray GB elementary composition [22,66,45,67,68] also effectively observe various properties that can cause changes in GB electrical behaviors, or directly characterize GB electrical parameters (Table 1). KPFM observation on polycrystalline CH 3 NH 3 PbI 3 films frequently showed significant differences in surface potential between GBs and GIs.…”
Section: Eismentioning
confidence: 99%